Death and Memory as Narrative Devices in Los recuerdos del porvenir, by Elena Garro - Barrera Enderle, Víctor (2024)
Los recuerdos del porvenir (1963), by Elena Garro, is one of the most discussed (and perhaps least read) novels of modern Mexican narrative. The work signified the author’s entry into the field of narrative, occupying, since then, a central place in Mexican literature. This article analyzes the narrative strategies deployed within the novel to describe the way in which the main narrator, the town of Ixtepec, is stealthily displaced by the inhabitants and characters of the text.